Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .